Necrostatin-1 Reduces Neurovascular Injury after Intracerebral Hemorrhage - Melanie D. King; Wittstatt A. Whitaker-Lea; James M. Campbell; Cargill H. Alleyne; Krishnan M. Dhandapani (International Journal of Cell Biology)
Intracerebral hemorrhage (ICH) is the most common form of hemorrhagic stroke, accounting for 15% of all strokes. ICH has the highest acute mortality and the worst long-term prognosis of all stroke subtypes. Unfortunately, the dearth of clinically effective treatment options makes ICH the least treatable form of stroke, emphasizing the need for novel therapeutic targets. Recent work by our laboratory identified a novel role for the necroptosis inhibitor, necrostatin-1, in limiting neurovascular injury in tissue culture models of hemorrhagic injury. In the present study, we tested the hypothesis that necrostatin-1 reduces neurovascular injury after collagenase-induced ICH in mice. Necrostatin-1 significantly reduced hematoma volume by 54% at 72 h after-ICH, as compared to either sham-injured mice or mice administered an inactive, structural analogue of necrostatin-1. Necrostatin-1 also limited cell death by 48%, reduced blood-brain barrier opening by 51%, attenuated edema development to sham levels, and improved neurobehavioral outcomes after ICH. These data suggest a potential clinical utility for necrostatin-1 and/or novel necroptosis inhibitors as an adjunct therapy to reduce neurological injury and improve patient outcomes after ICH.